HA (hyaluronic acid) fillers in aesthetic medicine - the most common complications - Szwed, Monika; Szwed, Weronika; Szwed, Jakub; Miga, Nadia (Journal of Education, Health and Sport, 2022)
Introduction and purpose Hyaluronic acid (HA) is a polysaccharide consisting of the disaccharide units of glucuronic acid and N-acetylglucosamine. The age-related changes in the different anatomical layers of the face can be treated with hyaluronic acid fillers. Knowing the predictable aging changes of the face is crucial as this guides the optimum filler choice. HA is currently the most common used filler worldwide. The aim of the study is to discuss the most common complications following aesthetic medicine treatments with the use of hyaluronic acid. Description of the state of knowledge Filling soft tissues with hyaluronic acid is a popular procedure in the field of aesthetic medicine for patients who want non-invasive rejuvenation. Among the numerous fillers, those with hyaluronic acid (HA) have many advantages: HA is easy to use and its effect is reversible. HA fillers are considered safe, although there may be complications such as: allergic reactions, infections, granulomas, nodules, tyndall effect, ecchymosis and skin necrosis. Many complications with the HA filler are correctable, for example: too little formulation, over-correctionand, asymmetry. Hyaluronic acid fillers are examples of reversible dermal fillers as they can be removed with hyaluronidase. Summary Avoiding complications is a top priority and must start with a thorough understanding of the anatomy followed by a precise injection technique. The ability to recognize complications and manage protocols will allow for their effective treatment.